Analysis of Two-Component Systems in Group B Streptococcus Shows That RgfAC and the Novel FspSR Modulate Virulence and Bacterial Fitness - Cristina Faralla (American Society for Microbiology, 2014)
ABSTRACT Group B Streptococcus (GBS), in the transition from commensal organisms to pathogens, will encounter diverse host environments and, thus, require coordinated control of the transcriptional responses to these changes. This work was aimed at better understanding the role of two-component signal transduction systems (TCS) in GBS pathophysiology through a systematic screening procedure. We first performed a complete inventory and sensory mechanism classification of all putative GBS TCS by genomic analysis. Five TCS were further investigated by the generation of knockout strains, and in vitro transcriptome analysis identified genes regulated by these systems, ranging from 0.1% to 3% of the genome. Interestingly, two sugar phosphotransferase systems appeared to be differentially regulated in the TCS-16 knockout strain (TCS loci were numbered in order of their appearance on the chromosome), suggesting an involvement in monitoring carbon source availability. High-throughput analysis of bacterial growth on different carbon sources showed that TCS-16 was necessary for the growth of GBS on fructose-6-phosphate. Additional transcriptional analysis provided further evidence for a stimulus-response circuit where extracellular fructose-6-phosphate leads to autoinduction of TCS-16, with concomitant dramatic upregulation of the adjacent operon, which encodes a phosphotransferase system. The TCS-16-deficient strain exhibited decreased persistence in a model of vaginal colonization. All mutant strains were also characterized in a murine model of systemic infection, and inactivation of TCS-17 (also known as RgfAC) resulted in hypervirulence. Our data suggest a role for the previously unknown TCS-16, here named FspSR, in bacterial fitness and carbon metabolism during host colonization, and the data also provide experimental evidence for TCS-17/RgfAC involvement in virulence. IMPORTANCE Two-component systems have been evolved by bacteria to detect environmental changes, and they play key roles in pathogenicity. A comprehensive analysis of TCS in GBS has not been performed previously. In this work, we classify 21 TCS and present evidence for the involvement of two specific TCS in GBS virulence and colonization in vivo. Although pinpointing specific TCS stimuli is notoriously difficult, we used a combination of techniques to identify two systems with different effects on GBS pathogenesis. For one of the systems, we propose that fructose-6-phosphate, a metabolite in glycolysis, is sufficient to induce a regulatory response involving a sugar transport system. Our catalogue and classification of TCS may guide further studies into the role of TCS in GBS pathogenicity and biology.